The Risk Analysis of Work Accidents Using The Bowtie Method in The Ciputra Hospital Construction Project - Risda Yasinta Dewi; I Nyoman Dita Pahang Putra (Jurnal Teknik Sipil, 2024)
The condition of work accident risk is a critical factor that needs to be taken seriously. Related to the construction of the Ciputra Hospital Project located on Jl. Made Selatan - Citraland Surabaya, the Ciputra Hospital project is planned to be built on nine floors with a building area of 23,000 m2, which will allow for various occupational accident risks. So, a risk analysis is needed to identify hazards that can occur. In this study, data collection was carried out through interviews and also distribution questionnaires. Questionnaires are used to find probability and severity scales, and questionnaires are distributed to project expert staff. After obtaining the results from the questionnaire, a risk assessment is carried out by finding the probability index and severity index and then determining the category with the risk matrix. After determining the category, the analysis was carried out using the bowtie method. The result of this study is to determine the most dominant risks, namely workers being punctured by sharp equipment when installing formwork, workers falling from a height when installing formwork, and workers being hit by a bar bender machine when forming. After analyzing using the bowtie method, it was found that the causes of the risk of accidents that occurred included workers in a tired condition, lack of concentration, and carelessness, incomplete use of PPE, undisciplined workers at work, no safety at the job site, bad weather, inexperienced workers, poor machine conditions.